Najnowsze opowieści z Górnego Śląska – między sagą rodzinną, herstory i renarracją mitów - Czyżak, Agnieszka (Poznańskie Studia Polonistyczne. Seria Literacka, 2023)
The article contains considerations on contemporary everyday life in Silesia. Its main aim is the interpretation of novels written in the late 2010s, for instance Od jednego Lucypera (From the same devil) by Anna Dziewitt-Meller, Pokora by Szczepan Twardoch, Kajś. Opowieść o G.rnym Śląsku (Kajś. A Story of Upper Silesia) by Zbigniew Rokita. Those stories are genologically placed between a family saga, herstory and myth retelling, but the most important purpose for the authors was the recognition of the specific Upper Silesian culture, past and present experiences and visions of the local community.